PRESENCIA Y REPUTACIÓN DIGITAL EN SOCIAL MEDIA: COMPARATIVA EN EL SECTOR DE LA MODA - Dr. Joan Francesc FONDEVILA GASCÓN,Dr. Josep Lluís DEL OLMO ARRIAGA,Vanesa BRAVO NIETO (Fonseca, Journal of Communication, 2023)
Online management reputation begins to be assumed as a priority for companies that find social media and Internet influence the image that their audience have. H&M and Zara, as the main buyers of retail business, are not an exception. Their mentions in social media and e commerce sales show a high level influence.